2017
DOI: 10.3390/ijms18020416
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Dietary Supplements to Elevate or Activate Circulating Paraoxonases

Abstract: Low levels of paraoxonase 1 (PON1) have been associated with the development of several pathological conditions, whereas high levels have been shown to be anti-atherosclerotic in mouse models. These findings suggest that PON1 could be a good surrogate biomarker. The other members of the family, namely PON2 and PON3, the role of which has been much less studied, deserve more attention. This paper provides a systematic review of current evidence concerning dietary supplements in that regard. Preliminary studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 100 publications
1
12
0
3
Order By: Relevance
“…There are many ways to increase PON1 potency by nutritional, lifestyle, and pharmacological intervention . Lou‐Bonafonte and colleagues proposed different protocols with nutraceuticals and functional foods to enhance the protective role of PONs. However, the human body can be refractory to the consumption of nutrients aimed to enhance metabolic and other enzymatic activities including those of the PONs.…”
Section: Resultsmentioning
confidence: 99%
“…There are many ways to increase PON1 potency by nutritional, lifestyle, and pharmacological intervention . Lou‐Bonafonte and colleagues proposed different protocols with nutraceuticals and functional foods to enhance the protective role of PONs. However, the human body can be refractory to the consumption of nutrients aimed to enhance metabolic and other enzymatic activities including those of the PONs.…”
Section: Resultsmentioning
confidence: 99%
“…La aterosclerosis es un desorden crónico de la pared arterial que comienza con la acumulación de grasa y gradualmente se forman placas ateroscleróticas. El nivel de HDL en plasma está inversamente correlacionado con la aterosclerosis, su efecto benéfico es en gran parte atribuido a su propiedad antioxidante mediada por la PON1 9 .…”
Section: Acción De La Pon1 En Enfermedad Cardiovascularunclassified
“…Es bien conocida la relación entre el desarrollo de la aterosclerosis y las lipoproteínas de baja densidad (LDL), así como la función ateroprotectora de las HDL, puesto que son encargadas del transporte reverso del colesterol y también por su contenido de proteínas antioxidantes, dentro de las cuales la PON1 es la que presenta una mayor actividad antioxidante 9 .…”
Section: Acción De La Pon1 En Enfermedad Cardiovascularunclassified
“…Beyond the Hp2-2 genotype, other genotypes may affect the outcome of vitamin E supplementation. Several studies demonstrated an impact of e.g., apolipoprotein E (ApoE) genotype [ 246 , 247 , 248 ] and Paraoxonase 1 (PON-1) genotype [ 249 , 250 ] on vitamin E. For example, the apoE4 genotype represents a significant risk factor for CVD. ApoE4 may be associated with lower vitamin E retention in peripheral tissues, possibly related to a combination of several factors: An increased α-TOH retention in LDL, an impaired cellular vitamin E delivery system, a reduced expression of lipoprotein receptors, and an increased intracellular degradation of vitamin E [ 248 ].…”
Section: Controversial Outcome Of Rcts—explanatory Approachesmentioning
confidence: 99%